2022
DOI: 10.1186/s42825-022-00105-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol based hybrid nano-aggregates modified collagen fibers of biological valve leaflets to achieve enhanced mechanical, anticoagulation and anti-calcification properties

Abstract: Glutaraldehyde (Glut)-crosslinked porcine pericardium and bovine pericardium are mainly consisted of collagen and widely used for the preparation of heterogenous bioprosthetic heart valves (BHV), which play an important role in the replacement therapy of severe valvular heart disease, while their durability is limited by degeneration due to calcification, thrombus, endothelialization difficulty and prosthetic valve endocarditis. Herein, we develop a novel BHV, namely, TPly-BP, based on natural tannic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The hemolysis ratio is an essential factor to consider for the clinical application of blood-contacting devices. 43 To determine the hemolytic effect of the CQPU and CMPU coatings, all samples were exposed to diluted erythrocytes for 1 h. As displayed in Fig. 8b, the hemolysis ratio of the CQPU coating exhibited a high hemolysis ratio of 23.1%.…”
Section: Resultsmentioning
confidence: 99%
“…The hemolysis ratio is an essential factor to consider for the clinical application of blood-contacting devices. 43 To determine the hemolytic effect of the CQPU and CMPU coatings, all samples were exposed to diluted erythrocytes for 1 h. As displayed in Fig. 8b, the hemolysis ratio of the CQPU coating exhibited a high hemolysis ratio of 23.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Following publication of the original article [3], it was found in the 'Ethics approval and consent to participate' section is incorrect, the correct 'Ethics approval and consent to participate' section is provided below:…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…Metallic‐polyphenolic nanoparticles provide an effective approach [ 19 ] to prepare multifunctional hydrogels, which is a simple green process that can combine metal ions [ 20 ] and functional plant polyphenols [ 21,22 ] by adjusting the preparation conditions of ions and polyphenols. [ 23 ] Researchers have demonstrated that both metal ions and plant polyphenols have strong reversible interactions with CG molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The introduction of crosslinkers is a simple and effective method for advanced CG modification, and some researchers use this method to improve various properties of CG, such as moisturizing, antibacterial, anti-inflammatory, etc., but unsatisfactory. [17,18] Metallic-polyphenolic nanoparticles provide an effective approach [19] to prepare multifunctional hydrogels, which is a simple green process that can combine metal ions [20] and functional plant polyphenols [21,22] by adjusting the preparation conditions of ions and polyphenols. [23] Researchers have demonstrated that both metal ions and plant polyphenols have strong reversible interactions with CG molecules.…”
Section: Introductionmentioning
confidence: 99%